(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article devoted to achievements of translation of Uzbek stories and works into English. It is clear that Uzbek has great and wealth literature and delivering the works to foreigners is one of important goals of our country. Additionally, there are given some information about achievements of best writers for translating.